Molecular characterization of mixed-histology endometrial carcinoma provides prognostic and therapeutic value over morphologic findings - Paulina J. Haight; Ashwini Esnakula; Courtney J. Riedinger; Adrian A. Suarez; Jessica Gillespie; Ashley Patton; Alexis Chassen; David E. Cohn; Casey M. Cosgrove (npj Precision Oncology)
Abstract We performed molecular analysis of a single-institution cohort of clinically diagnosed mixed-histology endometrial carcinoma (MEC). A gynecologic pathologist confirmed that 72 cases met diagnostic criteria for MEC based on WHO 2020 guidelines, and these were molecularly classified using both a DNA-based and histologic approach. Tumors were classified as: POLE-mutated (13.9%), microsatellite instability (MSI)-high/mismatch repair deficient (MMRd) (26.4%), TP53/p53 abnormal (p53abnl) (48.6%), no specific molecular profile (NSMP) (11.1%). Recurrence risk significantly differed based upon molecular class, but not histology. 44% of MEC cases had a HER2 IHC score of 2–3+, and this was not limited to p53abnl tumors. Transcriptional analysis demonstrated 93 differentially expressed genes between p53abnl and NSMP tumors, including many associated with the innate immune response and DNA damage repair. While p53abnl and NSMP tumors have similarly poor outcomes, transcriptome analysis revealed biologic differences that could impact targeted therapeutics in this high-risk group.